PENGARUH PENGGUNAAN MEDIA MEDIA PEMBUAT RODA PUTAR TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V DI SDN 186 PALEMBANG - Malik, Nur Fitri Qhoirunnisa Abdul; Effendi, Darwin; Pratiwi, Etty (Jurnal Dikdas Bantara, 2024)
This study aims to determine the significant effect of students' creative thinking skills between class V.A as the control class and class V.B as the experimental class using the rotating wheel media at SDN 186 Palembang. This study uses a True Experimental Design treatment design with a Posttest-Only Control Design design. The study population was all fifth grade students of SDN 186 Palembang totaling 99 students in the 2023/2024 academic year. The sampling technique used was simple random sampling. The validity test of the instrument was tested by calculating the Product Moment Person correlation and to determine its reliability, it was tested using the Cronbach's Alpha method. The data analysis technique used the t-test (Paired Sample T-Test), which had previously been known for its normality and homogeneity. The results of the experimental group study obtained an average score of 78.73 and the control group obtained an average posttest score of 50.15, so it can be concluded that there is a significant influence on students' creative thinking skills in learning Indonesian language for grade V on advertising materials at SDN 186 Palembang in the even semester of the 2023/2024 academic year.